The Time Constraint in Conference Interpreting: Simultaneous vs. Consecutive - Gumul, Ewa; Łyda, Andrzej (Research in Language, 2007)
The present paper focuses on the concept of time constraint in interpreting. The main aim of the study is to compare the two modes of interpreting, i.e. consecutive and simultaneous in terms of the temporal load imposed by the operations constituting each of them. The discussion centres on the issues of external pacing and processing capacity management, the two focal points of The Time Constraint. The paper also examines a range of strategies interpreters resort to in order to minimise the impact of time pressure in both CI and SI, such as EVS regulation, economy of expression, text-editing strategies, and notation techniques.